THE STAR OF BETHLEHEM - Pescali, Piergiorgio (IJRDO - Journal of Social Science and Humanities Research, 2016)
“Now after Jesus was born in Bethlehem of Judea in the days of Herod the king, behold, wise men from the East came to Jerusalem, saying, Where is He who has been born King of the Jews? For we have seen His star in the East and have come to worship Him. When Herod the king heard this, he was troubled, and all Jerusalem with him.And when he had gathered all the chief priests and scribes of the people together, he inquired of them where the Christ was to be born.” (Mt 2, 1-4)